COVID-19 acute respiratory distress syndrome: can iloprost have a role for the treatment?. (2021) - Filippini, Alida; Bnà, Claudio; Bellosta, Raffaello; Bazzani, Roberto; Luzzani, Luca; Pegorer, Matteo Alberto; Zandalasini, Matteo; Baldon, Michela; Codazzi, Manuela; Sabatini, Tony
Abstract: Pulmonary infection of 2019-nCoV can frequently induce acute respiratory distress syndrome (ARDS) with partial pressure of arterial oxygen/fraction of inspired oxygen ratio (pO2/FiO2) of less than 300 mmHg. Moreover, it can be complicated with cardiac injury or arrhythmia, microvascular and large-vessel thrombosis. We describe a case of a patient with COVID19-ARDS and concomitant critical ischemia of the limbs. Iloprost treatment, an analogue of a prostacyclin PGI2, was started for residual left forefoot ischemia after surgical thromboembolectomy. Unexpectedly, we documented improvement of respiratory performance and lung high resolution computed tomography (HRCT) showed significant regression of the diffuse pulmonary ground-glass opacity. The hypothetical mechanism is that iloprost can enhance perfusion preferentially to well-ventilated lung regions, reduce pressures of peripheral pulmonary vessels and induce reduction of lung interstitial edema. In addition, iloprost antithrombotic effect, endothelial damage repairing and neo-angiogenesis activity could play a relevant role.